PERAN PTK-PNF DALAM MENGHADAPI KERAGAMAN SOSIAL BUDAYA: Sebuah Perenungan Seabad Kebangkitan Nasional - Waspodo, Muktiono (JIV-Jurnal Ilmiah Visi, 2008)
Indonesia has variety of social and cultural backgrounds which become the strength of the nation. This pluralism should be acknowledged and developed harmoniously. This article discusses how non-formal education should play its role in transforming the pluralism value to the Indonesian people, specifically how to conduct learning process based on the social and cultural pluralism.